Development of Competence Skills of Art Education Students - Berikbaev, Аlisher Аlikulovich (International Journal of Psychosocial Rehabilitation, 2020)
Present day developed world’s market economics in competitive conditions demands specialists who have critical thinking, creativeness and leader abilities to solve different kind of issues. This article seeks to shed light on what a future art teacher should be and what it should focus on, what pedagogical competence should be, whether it is competent, how it should be shaped and developed, and whether we can respond to today’s reforms. In this article is given information, how should be modern art teachers and what aspects they should know to develop their competence. Besides, in this article author tried to show results of reforms in field of education which is in progress in modern Uzbekistan’s social life.